Analisis Kompetensi Profesional Guru Biologi SMA Negeri Se-Kabupaten Deli Serdang - Manullang, Hengki Frengki; Harahap, Fauziyah; Djulia, Ely (Jurnal Pendidikan Biologi, 2017)
The purpose of this study is to look at the professional competenceof Biology teachersof State Senior High School in Deli Serdang based on gender, age, working period, certification and the graduation level. The population in this study were allBiology Teachers of Senior High School in Deli Serdang which had 56 teachers. The sample was purposive sampling with 53 teachers, 318 peer teachers, 3 lecturers as the expert of validators. Descriptive qualitative research was applied.Data were collected by using the test which covered written comprehension test of professionalcompetence. The findings showed that the professional competence of biology teachers were competent based on Permendiknas No. 16 Year 2007.The results of professional competence of teachers was 75 categorized as competent enough which covered  written comprehension  test,  in  Grade 10 was 75 categorized as competent, Grade 11 was 75 categorized as competent, and Grade 12 was 74 categorized as  competent enough. The professional competence test of the teachers showed that (1) male teachers were more competent rather than female ones, (2) medium age of teachers were more competent rather than young age and old one, (3) 13 up to 24 years working period were more competent rather than 1 up to 12 years as well as  25 up to 36 years, (4) certification of teachers were more competent rather than not certification, (5) Postgraduate graduations were more competence rather than undergraduate  ones. This study implicated to be sustainable development for biology teachers of State Senior high school in Deli Serdang.